Television, nation, and culture in Indonesia - Kitley, Philip, 1946- (Ohio University Center for International Studies, 2000)
The culture of television in Indonesia began with its establishment in 1962 as a public broadcasting service. From that time, through the deregulation of television broadcasting in 1990 and the establishment of commercial channels, television can be understood, Philip Kitley argues, as a part of the New Order's national culture project, designed to legitimate an idealized Indonesian national cultural identity. But Professor Kitley suggests that it also has become a site for the contestation of elements of the New Order's cultural policies. Based on his studies, he further speculates on the.
Keywords: Television broadcasting -- Indonesia.; Television broadcasting policy -- Indonesia.; Television programs -- Indonesia.; Télévision -- Indonésie.; Télévision -- Politique gouvernementale -- Indonésie.; Émissions télévisées -- Indonésie.; TECHNOLOGY & ENGINEERING -- Television & Video.; PERFORMING ARTS -- Television -- History & Criticism.; Television broadcasting; Television broadcasting policy; Television programs; Indonesia; Geschichte; Indonesien; Fernsehen; Televisie.; Politique de la télédiffusion -- Indonésie.; Télévision -- Émissions -- Indonésie.